1998
DOI: 10.2307/120987
|View full text |Cite
|
Sign up to set email alerts
|

Positivite et Discretion des Points Algebriques des Courbes

Abstract: Soient K un corps de nombres et K sa clôture algébrique. Soient X K une courbe propre, lisse, géométriquement connexe de genre g ≥ 2 sur K et J sa jacobienne. Soit D 0 un diviseur de degré 1 sur X et φ D 0 le plongement de X K dans J défini par D 0 . On note h N T (x) la hauteur de Néron-Tate d'un point x ∈ J(K). On montre dans ce texte l'énoncé suivant qui aété conjecturé par Bogomolov [2]:Notons que Raynaud [10] a prouvé que l'ensemble des points P ∈ X K (K) tels que φ D 0 (P ) est de torsion dans J est fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
10

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 18 publications
3
106
0
10
Order By: Relevance
“…Notably, equidistribution played a key role in the proof by Ullmo [89] and Zhang [98] of the Bogomolov conjecture. In the other direction, Ratazzi-Ullmo [75] give a proof of MM using methods developed for AO.…”
Section: Theorem Letmentioning
confidence: 99%
“…Notably, equidistribution played a key role in the proof by Ullmo [89] and Zhang [98] of the Bogomolov conjecture. In the other direction, Ratazzi-Ullmo [75] give a proof of MM using methods developed for AO.…”
Section: Theorem Letmentioning
confidence: 99%
“…Conjecture 1.1 fits into Zhang's far-reaching system of dynamical conjectures [Zha06]. Zhang's conjectures include dynamical analogues of the Manin-Mumford and Bogomolov conjectures for abelian varieties (now theorems of Raynaud [Ray83a,Ray83b], Ullmo [Ull98], and Zhang [Zha98]), as well as a conjecture about the Zariski density of orbits of points under fairly general maps from a projective variety to itself. This latter conjecture of Zhang takes the following form in the case of polynomial actions on A g .…”
Section: Introductionmentioning
confidence: 98%
“…Conjecture 1.1 fits into Zhang's far-reaching system of dynamical conjectures [36]. Zhang's conjectures include dynamical analogues of the Manin-Mumford and Bogomolov conjectures for abelian varieties (now theorems of Raynaud [25,26], Ullmo [33], and Zhang [35]). We note that two of the authors found counterexamples to Zhang's original Dynamical Manin-Mumford and Bogomolov conjectures; a reformulation of those two conjectures will soon appear due to work of Ghioca, Tucker and Zhang [13].…”
Section: Conjecture 11 (The Cyclic Case Of the Dynamical Mordell-lanmentioning
confidence: 95%